Effect of thermocycling on the bond strength of a glass-infiltrated ceramic and a resin luting cement Efeito da ciclagem térmica sobre a resistência de união entre uma cerâmica infiltrada com vidro e um cimento resinoso - Osvaldo Daniel Andreatta Filho; Marco Antonio Bottino; Renato Sussumu Nishioka; Luiz Felipe Valandro; Fabíola Pessoa Pereira Leite (University of São Paulo, 2003)
The aim of the present study was to evaluate the effect of thermocycling on the bond strength between the surface of the glass-infiltrated alumina ceramic In-Ceram (VITA) and the Panavia F resin cement (Kuraray CO.). Four 5x6x6mm In-Ceram blocks were obtained. One of the 6x6mm faces of each block was conditioned with Cojet - System (tribochemical silica coating, ESPE-3M) and then luted under a constant 750g pressure with Panavia F cement to another identical face of a resin composit block (Clearfil AP-X, Kuraray) obtained by reproduction of the ceramic one from Express (3M) addition curing silicone impressions. The four sets so formed by ceramic, luting cement and resin have been each one serially sectioned in 20 sticks so that the adhesive surface in each presented 1mm² of area. The samples were divided in 2 groups (n=10): G1- stored for 7 days in deionized water at 36 ± 2ºC; G2 - thermocycled 1500 times between 5 and 55ºC dwell times. The microtensile tests were accomplished in an universal testing machine (EMIC) at a crosshead speed of 0,5 mm/min. The results showed that the mean tensile bond strength values (MPa) for the group G2: (22,815 ± 5,254) had not statistically differ of the values of group G1: (25,628 ± 3,353) (t = 1,427; gl = 18; p-value = 0,171), at the level of a= 5%. It can be concluded that the thermocycling technique used in the present experiment had not produced statistically significant differences between the bond strength results of the specimens obtained by the two used techniques. O objetivo deste estudo foi avaliar o efeito da ciclagem térmica sobre a resistência de adesão entre a superfície da cerâmica In-Ceram Alumina (VITA) e o cimento resinoso Panavia F (Kuraray). Foram confeccionados quatro blocos de cerâmica In-Ceram com dimensões de 5x6x6mm. Uma das faces com 6x6mm de cada bloco cerâmico, após condicionamento com o sistema Cojet (ESPE-3M) (jateamento com óxido de alumínio/jateamento com óxido de sílica/ silanização) foi cimentada com Panavia F, sob peso constante de 750g, a outro bloco idêntico de resina composta Clearfil AP-X (Kuraray). Os blocos de resina foram obtidos por meio de duplicação daqueles de cerâmica a partir de moldes com silicona de adição Express (3M). Os quatro conjuntos formados por cerâmica, cimento e resina foram seccionados em 20 corpos-de-prova com forma de palitos, de modo que a região adesiva apresentasse 1mm² de área. Dois grupos (n=10) foram constítuidos: G1- estocagem por 7 dias em água deionizada à 36 ± 2ºC; G2- 1500 ciclos entre 5ºC e 55ºC com intervalos de 30 segundos. A seguir, foi realizado o teste de microtração em máquina de ensaio universal (EMIC) com velocidade de 0,5 mm/min. Os resultados mostraram que os valores médios de tensão de ruptura (MPa) para o grupo G2: (22,815 ± 5,254) não tiveram diferenças estatisticamente significantes daqueles do grupo G1: (25,628 ± 3,353) (t= 1,427; gl = 18; p-valor = 0,171), ao nível de significância de 5%. A partir destes resultados, entendemos lícito concluir que o efeito da ciclagem térmica não produziu alterações estatisticamente significantes nos valores da resistência adesiva.